CLUSTERING TECHNIQUE AND PEER ASSESSMENT IN TEACHING WRITING RECOUNT TEXT TO JUNIOR HIGH SCHOOL STUDENTS - Widyawati, Eka Yunita; Trisanti, Novia (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
This study was conducted under the consideration of the observation in SMPN 39 Semarang that many students faced problems in learning to write a text. This research is aimed at investigating the effectiveness of using clustering technique and peer assessment in teaching writing recount text compared to three-phase technique and the students’ perception of the lesson. A quasi-experimental was used as the research design in this study. The subjects were the eighth graders of SMPN 39 Semarang in the academic year of 2016/2017 with 60 students as the samples. The control group (VIIIC) was treated using three-phase technique and teacher assessment, while the experimental group (VIII D) was taught using clustering technique and peer assessment. The findings revealed that the use of clustering technique and peer assessment significantly improved the students’ achievement in writing recount text. It was proven by the result of t-test in which the t-value (4.31) was higher than t-table (2.00). In addition, based on the result of the questionnaire, 90% of the students agreed that the use of clustering technique and peer assessment improved the students’ writing achievement. All in all, the use of clustering technique and peer assessment is more effective for teaching writing recount text to junior high school students than three-phase technique and teacher assessment. Moreover, most of the students have a positive perception to the lesson.